Diplomske značke nekdanjih šol za medicinske sestre, otroške negovalke in babice v Sloveniji - Fischinger, Janez (Obzornik zdravstvene nege, 2017)
Introduction: Around the world schools of nursing and midwifery awarded their graduates with badges or pins. The pins are referred to with different names: school, nurse/midwives or graduation pins. The goal of this historical research was, in addition to preserving knowledge on this cultural tradition, also to establish which Slovenian schools presented these pins and what they looked like. Methods: There are almost no written sources related to this topic, so 346 interviews with currently employed nurses and midwives as well as retired nurses and midwives or their relatives were conducted. Photographs exhibiting pins on nurses or midwives uniforms were also collected. The research was conducted from June 2013 to December 2016. Results: It has been established that all graduates of Slovenian nursing and midwifery schools were presented with graduation pins. The earliest pins were awarded in 1925. After the educational reform of secondary schools in 1981/82 the pins were no longer presented. Five types of pins with different symbolic motifs were documented. Less than a fifth (19 %) of the interviewees still have the pins in their possession. Discussion and conclusion: The pins provide evidence of the foundation and development of healthcare schools and present a part of Slovenian nursing history. They should be put in a museum or maybe even in an independent museum of healthcare as it is customary elsewhere around the world.
Keywords: babice; babištvo; badges; Blennioidei; diplomske značke; graduation pins; medicinske sestre; midwifery; midwifes; nursery; nursery nurses; nurses; otroške sestre negovalke; pins; priponke; zdravstvena nega; značke